Analysis Of Meaning And Poetic Devices In The Poem “The Soldier” By Rupert Brooke - Robby Satria; Mhd Johan; Ramanda Rizki (LPPM Universitas Putera Batam, 2025)
This article analyzes the meaning and poetic devices of the poem